Women and work: ethical-legal considerations regarding the prevention of the reproductive risk - Di Pietro, Maria Luisa; Fisso, Maria Beatrice (Medicina e Morale, 1995)
By now it is well known that work can directly or indirectly intluence health. The awareness of this fact has led to increasing attention being paid to the harmful effects of "suspicious" substances in the work environment. This article deals with one particular aspect of the risks at work, and that is the risk following the woman's exposition to chemical substances or physical or biological agents that may alter her reproductive capacity or cause serious damage to the children who bave been or will be conceived. The authors make a distinction between the reproductive risk (the possibility that a substance may interfere with or prevent conception) and the risk of development (the possibility of producing structural anomalies, functional defects of death, in the unbom in fant or in the child up to puberty). The authors then analyse the action mechanism of the chemica stances and physical and biological agents found most frequently in work environments; they point out the moment of interference (oogenesis, pregnancy, breast feeding) and identify and critically examine the possible modalities of prevention of the reproductive and development risks. From the identification of the situation at risk to the definition of control measurcs necessary for reducing or eliminating the exposure of the workers, to providing in formation regarding the existence and extent of the risk: this is an analysis which - from a personalistic point of view, also in the light of laws in force at present - seems to indicate new ways to really protect women workers and to carry out a real fetal protection policy.